2016
DOI: 10.1016/j.trecan.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Intergenically Spliced Chimeric RNAs in Cancer

Abstract: Gene fusions and their encoded products (fusion RNAs and proteins) are viewed as one of the hallmarks of cancer. Traditionally, they were thought to be generated solely by chromosomal rearrangements. However, recent discoveries of trans-splicing and cis-splicing events between neighboring genes, suggest that there are other mechanisms to generate chimeric fusion RNAs without corresponding changes in DNA. In addition, chimeric RNAs have been detected in normal physiology, complicating the use of fusions in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 81 publications
(94 reference statements)
0
84
1
Order By: Relevance
“…Surprisingly, we found DNA support for only 6 of 242 fusions for which genomic data was available (Table 3). Fusions specific to RNA are increasingly reported in cancers and normal cell lines (Babiceanu et al 2016;Grosso et al 2015;Jia et al 2016;Li et al 2008;Qin et al 2015;Yun et al 2014). Similarly, in our study we have not been able to identify DNA support for most fusion events, suggesting they appear exclusively in the transcriptome.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Surprisingly, we found DNA support for only 6 of 242 fusions for which genomic data was available (Table 3). Fusions specific to RNA are increasingly reported in cancers and normal cell lines (Babiceanu et al 2016;Grosso et al 2015;Jia et al 2016;Li et al 2008;Qin et al 2015;Yun et al 2014). Similarly, in our study we have not been able to identify DNA support for most fusion events, suggesting they appear exclusively in the transcriptome.…”
Section: Discussioncontrasting
confidence: 66%
“…ReadThroughs form via cis-splicing, while trans-splicing of two separately transcribed pre-mRNA molecules can drive RNA-specific formation of fusions typically thought to be caused by genomic restructuring, such as CodingFusions (Gingeras 2009;Li et al 2008). Cissplicing, trans-splicing and splicing to produce truncated-and NoHeadGene-like fusions have all been previously reported in various cancers (Bartonicek et al 2017;Li et al 2008;Jia et al 2016;Qin et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…4A). The genomic proximity of identified transcripts suggests that these fusions could be a result of cis-splicing (7,12). Inspection of nucleotide sequences located 5' and 3' of the fusion junctions for canonical splicing donors (GT) and acceptors (AG) revealed that 81.9% carried GT and AG at the 5' and 3' fusion sites (GT*AG) (Fig.…”
Section: Fusion Transcripts With Splicing Motifs Are Enriched In Neurmentioning
confidence: 98%
“…Besides a fusion resulting from small interstitial genomic deletions at 11q generating either a MLL-FOXR1 or a PAFAH1B2-FOXR2 fusion (11) no intra-chromosomal chimeric transcripts have been described in neuroblastoma. However, they have been shown to be present in other tumor types as well as in non-transformed tissues and be promoted by different types of cellular stress such as infections or mutations (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The ETV6-NTRK3 fusion was present in a head and neck thyroid carcinoma sample, linking exon 4 of ETV6 to exon 12 of NTRK3. We found three separate SVs in the same sample: i) a translocation of ETV6 (chr12:12,099,706) to chromosome 6 (chr6:125,106,892); ii) a translocation of NTRK3 (chr15:88,694,049) also to chromosome 6 (chr6:125,062,387); and iii) an additional copy number loss (chr12:12,032,501 -chr12:12,099,705) spanning from ETV6 intron 5 to the exact SV breakpoints (chr12:12,099,706), jointly bringing ETV6 within 45 kb upstream of NTRK3, a distance that would allow transcriptional read-through 71 or splicing 72 to yield the ETV6-NTRK3 fusion 73 (Figure 5d). Thus, the short chromosome 6 segment appeared to function as a bridge, linking two other genomic locations to facilitate a gene fusion.…”
Section: Bridged Fusions and Evidence-based Gene Fusion Classificationmentioning
confidence: 99%